2021
DOI: 10.1136/openhrt-2020-001522
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary use of excimer laser in percutaneous coronary intervention with indications, procedural characteristics, complications and outcomes in a university teaching hospital

Abstract: BackgroundExcimer laser coronary atherectomy (ELCA) can be used as an adjunctive percutaneous coronary intervention treatment for challenging, heavily calcified lesions. Although previous studies have documented high rates of complication and restenosis, these predate the introduction of the smaller 0.9 mm laser catheter. As the coronary complexity has increased, there has been a renewed interest in the ELCA. This study investigates the indications, procedural characteristics, complications and outcomes of ELC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Similar to previous studies our analysis showed that the most common indication for ELCA PCI use was calcific/uncrossable lesions and as such the most frequently used catheter is the 0.9 mm device given this is highly deliverable with option for high fluence and frequency of energy delivered to achieve modulation of the lesion. 2,10 ELCA PCI for thrombus indication is an effective and safe technique but remained at a low level during our study timeframe largely because of the absence of prospective clinical data to support use in these patients. Interestingly, in a small study comparing manual thrombus aspiration and ELCA in patients with STEMI, Shimojo et al demonstrated that ELCA PCI was associated with a reduced creatine kinase and improved LV function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previous studies our analysis showed that the most common indication for ELCA PCI use was calcific/uncrossable lesions and as such the most frequently used catheter is the 0.9 mm device given this is highly deliverable with option for high fluence and frequency of energy delivered to achieve modulation of the lesion. 2,10 ELCA PCI for thrombus indication is an effective and safe technique but remained at a low level during our study timeframe largely because of the absence of prospective clinical data to support use in these patients. Interestingly, in a small study comparing manual thrombus aspiration and ELCA in patients with STEMI, Shimojo et al demonstrated that ELCA PCI was associated with a reduced creatine kinase and improved LV function.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several retrospective cohorts and case series that have demonstrated the short-term efficacy of ELCA. [8][9][10][11][12][13][14][15] The largest study to date is based on the National Cardiovascular Data Registry (NCDR) which demonstrated that the use of ELCA PCI was associated with a higher frequency of periprocedural complication. 14 Similarly, the British Cardiovascular Intervention Society (BCIS) database (from 2010 to 2016) demonstrated an increased risk of periprocedural complications but not major short-term adverse cardiac/cerebrovascular events with the use of ELCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation